"Lay epidemiology": an important factor in Danish parents' decision of whether to allow their child to receive a BCG vaccination. A qualitative exploration of parental perspective - Gitte Thybo Pihl; Helle Johannessen; Jette Ammentorp; Jane Schmidt Jensen; Poul-Erik Kofoed (BMC, 2017)
Abstract Background Vaccination is used worldwide to prevent infectious diseases. However, vaccination programmes in western countries face challenges in sustaining high coverage rates. The aim of this study was to explore how parents in Denmark make a decision about whether to allow their child to receive a Bacille Calmette Guerin vaccine at birth for the purpose of achieving non-specific effects on the immune system. Methods A total of five focus groups were conducted with expectant mothers and fathers. Written information about the vaccine and information about the hypothesis of non-specific effects of the vaccine were delivered in order to discuss considerations and determinants of parents' decisions. Results Heritable factors and the possibility of stimulating the immune system of the child to achieve less atopic diseases and fewer infections were identified as arguments in favour of receiving the BCG vaccine. Arguments against receiving BCG mainly focused on concerns about its described and non-described side effects. Both arguments for and arguments against the vaccine were seen as parents attempt to make an individual risk evaluation for their child. Attitudes and beliefs in the local network were identified as important for parents' decisions. Discussion It is discussed how "lay epidemiology" characterizes parents' risk evaluation as an individual addition to the population-based risk declaration. It is furthermore discussed how health professionals should engage with both the empirical element and the value element of "Lay epidemiology". Conclusion "Lay epidemiology" forms the basis for the parental decision of whether to allow their child to receive a BCG vaccination. Attitudes and beliefs about the causes and distribution of illnesses in the family or local network influence parents' risk evaluations. It would be ideal for parents if health professionals focused their communication about the BCG vaccine on individual risk evaluations.